PELUANG ADOPSI SISTEM AGROFORESTRY DAN KONTRIBUSI EKONOMI PADA BERBAGAI POLA TANAM HUTAN RAKYAT DI KABUPATEN CIAMIS - Budiman Achmad; Ris Hadi Purwanto (Environmental Research Center (PPLH) of Udayana University, 2014)
Agroforestry system as well as the potential species and the corresponding economic valuesin Ciamis District are very diverse. To encourage farmers adopt agroforestry system, botheconomical and environmental advantages have to be promoted. This research wasconducted at April to July 2010 at Ciomas, Kalijaya and Kertaharja villages in the Panjalu,Banjarsari, and Cimerak sub-Districts respectively. Primary and secondary data wereanalyzed by quantitative and qualitative descriptive. The result showed that the highertopography, the more simple agroforestry system applied. The narrower forest size managed(strata 3), the higher chance agroforestry system adopted by farmers. Farmers in the highand low topography (Northern and Southern Ciamis regions) had higher chance to adoptagroforestry system, while the moderate topography showed lower adoption chance. Theeconomic contribution of non-forest products (NFPs) influences strongly the farmer decisionto adopt agroforestry system. The highest economic contribution of Paraserienthesmoluccana was 42.71% in Kalijaya, while the highest economic contribution of non-forestproduct was 75.00 % in Ciomas.